Heritage Tourism: Typology and Supply Side Issues - Riley, Ray (Turyzm/Tourism, 2007)
In order to classify the means by which tourists are able to experience heritage, a five tier typology ls presented: buildings, museum collections, open air museums, working museums, and the performing arts. Some supply-side issues facing heritage tourism in the UK are then discussed. These are: authenticity, education versus entertainment, re-enactment, glorious and difficult heritage, and the generation of income. It is concluded that much, if not all, heritage is presented responsibly to the tourist.